Extracellular vesicles with ubiquitinated adenosine A2A receptor in plasma of patients with coronary artery disease. Issue 10 (24th August 2019) - Ruf, Jean; Vairo, Donato; Paganelli, Franck; Guieu, Régis
Abstract: Extracellular vesicles (EV) can transfer cellular molecules for specific intercellular communication with potential relevance in pathological conditions. We searched for the presence in plasma from coronary artery disease (CAD) patients of EV containing the adenosine A2A receptor (A2A R), a signalling receptor associated with myocardial ischaemia and whose expression is related to homocysteine (HCy) metabolism. Using protein organic solvent precipitation for plasma EV preparation and Western blotting for protein identification, we found that plasma from CAD patients contained various amounts of EV with ubiquitin bound to A2A R. Interestingly, the presence of ubiquitinated A2A R in EV from patients was dependent on hyperhomocysteinemia, the amount being inversely proportional to A2A R expression in peripheral mononuclear cells in patients with the highest levels of HCy. CEM, a human T cell line, was also found to released EV containing various amounts of ubiquitinated A2A R in stimulated conditions depending on the hypoxic status and HCy level of culture medium. Together, these data show that ubiquitinated A2A R‐containing EV circulate in the plasma of CAD patients and that this presence is related to hyperhomocysteinemia. A2A R in plasma EV could be a useful tool for diagnosis and a promising drug for the treatment of CAD.